Designing A Website-Based School Health Business Information System Using The Wix Platform - Dedi Mulyadi; Ilyas, Ilyas; Wahyudin, Wahyudin (Yayasan Insan Mulia Bima, 2024)
This study aims to design a website-based School Health Enterprises (UKS) information system and determine the feasibility level of the website. The final result of this research is a website-based School Health Enterprises (UKS) information system using the Wix Platform at SMPN 1 Belo which has been tested for feasibility. This research is Research and Development. The stages in this study include five stages, namely (1) the requirements stage (needs analysis), (2) design, (3) implementation (website creation), (4) verification (product testing), and (5) maintenance ( product maintenance). Validation is carried out to determine the feasibility of the designed application. The tryout was carried out on 7 subjects consisting of school operators, teachers and several school officials (principal, UKS supervisory team, and teachers) at Belo 1 Middle School. The results of this study are (1) a website-based School Health Enterprises (UKS) information system using the Wix Platform at SMPN 1 Belo; (2) the quality of the designed website-based School Health Enterprises (UKS) information system is included in the very feasible category in terms of content and in terms of appearance, this is based on website feasibility assessments from material experts with a percentage of 83.52% and user ratings with a percentage of 98.44 %, the website-based School Health Enterprises (UKS) information system using the Wix Platform at Belo 1 Middle School was declared feasible for use.